William Edward Dodd papers - Dodd, William Edward, 1869-1940.; Sandburg, Carl, 1878-1967.
Correspondence, diaries, speeches, writings, autobiographical notes, printed matter, photographs, and other papers relating to Dodd's work as an author, professor of history at the University of Chicago, and U.S. ambassador to Germany (1933-1937). Subjects include local, state, national, and international politics. Includes letters written by Dodd during a trip to Europe (1928-1929). Includes poetry drafts by Carl Sandburg sent to Dodd's daughter, Martha Dodd (Stern). Family correspondents include his wife, Martha Johns Dodd, and their daughter, Martha. Other correspondents include Newton Diehl Baker, Carl L. Becker, Albert Jeremiah Beveridge, Claude Gernade Bowers, George P. Brett, Nicholas Murray Butler, Josephus Daniels, Edward Mandell House, Cordell Hull, R. Walton Moore, Franklin D. Roosevelt, Daniel C. Roper, Hjalmar Horace Greeley Schacht, and Frederick Jackson Turner.
Historian and diplomat.
Collection material in English and German, with French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Becker, Carl L. -- 1873-1945 -- Correspondence; Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Bowers, Claude Gernade, -- 1879-1958 -- Correspondence; Brett, George P. -- 1858-1936 -- Correspondence; Butler, Nicholas Murray, -- 1862-1947 -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Dodd, Martha, -- 1908-1990 -- Correspondence; Dodd, Martha Johns, -- -1938 -- Correspondence; House, Edward Mandell, -- 1858-1938 -- Correspondence; Hull, Cordell, -- 1871-1955 -- Correspondence; Moore, R. Walton -- 1859-1941 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roper, Daniel C. -- 1867-1943 -- Correspondence; Schacht, Hjalmar Horace Greeley, -- 1877-1970 -- Correspondence; Turner, Frederick Jackson, -- 1861-1932 -- Correspondence; Dodd family -- Correspondence; University of Chicago; Diplomatic and consular service, American -- Germany; World politics -- 20th century; Chicago (Ill.) -- Politics and government; Europe -- Description and travel; Germany -- Foreign relations -- United States; Illinois -- Politics and government; United States -- Foreign relations -- Germany; United States -- History; United States -- Politics and government -- 20th century; Diplomats; Historians